A novel semi-automatic segmentation protocol for volumetric assessment of alveolar cleft grafting procedures. Issue 5 (May 2017) - Janssen, Nard G.; Schreurs, Ruud; Bittermann, Gerhard K.P.; Borstlap, Wilfred A.; Koole, Ronald; Meijer, Gert J.; Maal, Thomas J.J.
Abstract: A novel protocol for volumetric assessment of alveolar cleft grafting procedures is presented. Eleven cone-beam computed tomography (CBCT) datasets of patients who underwent secondary alveolar cleft reconstructive surgery for a unilateral alveolar cleft were evaluated by two investigators. Residual bone volumes 1 year after surgery were analysed using a semi-automated technique in which preoperative CBCT datasets were superimposed on the postoperative scans using voxel-based registration. To define the correct boundaries of the alveolar cleft defect in the preoperative CBCT dataset, a mirror image of the preoperative CBCT dataset was superimposed on the preoperative CBCT dataset. For the difference in residual bone volume between the two observers, an intraclass correlation of 0.98 and a Dice coefficient of 0.89 were found. This study describes a reliable segmentation protocol for volumetric analysis of the alveolar cleft defect in patients with a unilateral alveolar cleft.